High Quality Targeted Temperature Management (TTM) After Cardiac Arrest - Taccone, Fabio Silvio; Picetti, Edoardo; Vincent, Jean-Louis (Critical care (London, England), 2020)
Targeted temperature management (TTM) is a complex intervention used with the aim of minimizing post-anoxic injury and improving neurological outcome after cardiac arrest. There is large variability in the devices used to achieve cooling and in protocols (e.g., for induction, target temperature, maintenance, rewarming, sedation, management of post-TTM fever). This variability can explain the limited benefits of TTM that have sometimes been reported. We therefore propose the concept of “high-quality TTM” as a way to increase the effectiveness of TTM and standardize its use in future interventional studies.